Arah Ekspansi Minimarket Prima Freshmart di Jabodetabek Cenderung ke Selatan - Atmaja, Dede Surya; Nurussalwa (Jurnal Informatika dan Bisnis, 2024)
This study aims to identify the spatial distribution of Prima Freshmart (PFM) minimarkets in Jabodetabek from 2013 to 2023 and the factors driving their dispersion. The methods used include: (1) weighted mean center and spatial standard deviation to determine the center and direction of distribution, and (2) geographically weighted regression (GWR) with minimarket distribution as the dependent variable, and population density, distance to toll roads, and distance to city centers as independent variables. Data were processed using Geographic Information System (GIS). The results show that (1) PFM minimarkets were predominantly distributed southward from 2013 to 2023, and (2) higher local R² values were observed in Bekasi Regency, the borders of Bogor Regency, South Tangerang, and Tangerang Regency, as well as the northern part of Tangerang Regency. The spatial distribution of PFM indicates that store location expansion strategies align with population growth patterns in suburban areas of Jabodetabek.